if one zero of polynomial (k^2=k)x^2+68x+6k is reciprocal of other, Find K
Answers
Answered by
1
Hola Anushkaaa,
→ p( x ) = ( k² + k )x² + 68x + 6k
Since, one zero is reciprocal of other, product of zeroes = 1
But, Product of Zeroes = 6k ÷ ( k² + k )
=> [ 6 ÷ ( k + 1 ) ] = 1
=> ( k + 1 ) = 6
=> k = 5
→ p( x ) = ( k² + k )x² + 68x + 6k
Since, one zero is reciprocal of other, product of zeroes = 1
But, Product of Zeroes = 6k ÷ ( k² + k )
=> [ 6 ÷ ( k + 1 ) ] = 1
=> ( k + 1 ) = 6
=> k = 5
anu5hka12:
well the ans for this is given as 5, anyways thanks
Anyway, nice to know that you learnt how it works
Similar questions